The state of emotional tension of tennis sportswomen-players of high qualification - Uliz'ko V.M; Korobeynikov G.V (Kharkov National Pedagogical University, 2010)
An analysis and distributing of sportswomen is presented to on by the degree of expressed a personality and situation anxiety. 40 sportswomen took part in research. The psychophysiological functional state of man is studied in the conditions of high psychoemotional tension. The features of psychological mood are examined taking into account personality descriptions of every sportsman. Sporting achievement is the result of cooperation of external (financial, material) and internal (attitude toward trainings, presence of genetic preconditions) factors. External factors are mediated influence on success and cause for a sportsman the subjective states with the proper conduct.